ANALISIS YURIDIS JUAL BELI TANAH DI KOTA BEKASI (STUDI PUTUSAN 461/PDT.G/2019/PN BKS) - Adjeng Sri Muliya; Novina Sri Indiraharti (Reformasi Hukum Trisakti, 2022)
According to the National Land Law, selling and buying land involves permanently transferring ownership of the land in exchange for a clearly stated price between the seller and the buyer. The question at hand is whether the parties' sales and purchases complied with the relevant land laws, as well as whether the judge's ruling on Number 461/Pdt.G/2019/PN BKS addressing the legality of selling and buying land complied with laws and regulations. This study, to describe secondary data, is a descriptive normative legal study. Additionally, a qualitative analysis and logical conclusion were drawn from the data. According to the study's findings, when considering the material terms of a deal, buying and selling between parties is deemed legal. purchase, but when considered in light of the stipulations of Government Regulation Number 24 of 1997 Article 37 Paragraph 1 and Regulation of the Minister of Agrarian Affairs Number 3 of 1997 Article 94 Paragraphs 1 and 2, it may be claimed that it does not meet the formal requirements of buying and selling. In this case, the judge ruled that the sale and purchase of land without a sale and buy document was not in compliance with the rules and regulations in force.